Hot Pursuit on the High Seas - Doyle, Peter Reese; Nang Chan Yeema (Colorado Springs, CO USA Focus on the Family Publishing, 1994)
Mark and Penny Daring and their friend David Curtis tangle with thieves over stolen treasures of Greece.
Keywords: Adult Fiction